Qur’anic Methodology in the Study of Comparative Religion Metodologi Quran dalam Kajian Perbandingan Agama - Anwari, Md. Abdur Rahman (Journal of Islam in Asia (E-ISSN 2289-8077), 2014)
Abstract The Holy Qur’Én is a unique source of knowledge. It has comparatively discussed various religions, religious thoughts and communities to settle the truth and dispute the false and wrong. The Qur’an has its own methodology in the study of comparative religion based on its views on world religions, methodological objectives, principles and approaches. Yet, there is some kind of unawareness on the part of most of the scholars of the significance of the Qur’Én in the field of comparative religion. This paper is devoted to discuss the methodological issues related to the comparative study of religions according to the Qur’Én. Keywords: The Qur’Én, Comparative Religion, Methodology, Objectives, Principles. ************************************************** Abstrak Kitab Suci al-Quran adalah sumber pengetahuan yang unik. Ia berbincang mengenai perbandingan pelbagai agama, pemikiran beragama dan komuniti untuk menegakkan kebenaran dan mempertikaikan kepalsuan. Al-Quran mempunyai kaedah kajian perbandingan agama tersendiri yang berdasarkan pandangannya terhadap agama-agama dunia, objektif metodologikal, prinsip dan pendekatannya. Namun, terdapat ketidaksedaran di pihak kebanyakkan ulama terhadap kepentingan al-Quran dalam bidang perbandingan agama. Karya ini ditumpukan kepada pembincangan isu-isu yang berkaitan dengan kajian metodologi perbandingan agama berdasarkan al-Quran. Kata Kunci: Al-Quran, Perdingan Agama, Metodologi, Objectif, Princip.